2008
DOI: 10.1002/art.23591
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of CCR2 in rheumatoid arthritis: A double‐blind, randomized, placebo‐controlled clinical trial

Abstract: Objective. CCR2 is a chemokine receptor expressed by monocytes, macrophages, and a subset of T cells. Its ligand, CCL2 (monocyte chemotactic protein 1), is abundantly present in the synovium of patients with rheumatoid arthritis (RA). Blocking CCR2 prevents CCL2-mediated chemotaxis in vitro and modulates arthritis in animal models of RA. In this study we examined the effects of CCR2 blockade on synovial inflammation in RA.Methods. The study was designed as a phase IIa clinical trial with a human CCR2 blocking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
129
2
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 199 publications
(140 citation statements)
references
References 34 publications
8
129
2
1
Order By: Relevance
“…Surprisingly, previous clinical studies using inhibitors or neutralizing Abs for CCR2 in RA showed limited amelioration for various reasons. For example, the administration of the therapeutic Ab MLN102 failed due to its inefficiency in fully covering the entire CCR2 repertoire (32). Another small molecule inhibitor of CCR2, MK0812, failed due to poorly tolerated off-target effects (33).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, previous clinical studies using inhibitors or neutralizing Abs for CCR2 in RA showed limited amelioration for various reasons. For example, the administration of the therapeutic Ab MLN102 failed due to its inefficiency in fully covering the entire CCR2 repertoire (32). Another small molecule inhibitor of CCR2, MK0812, failed due to poorly tolerated off-target effects (33).…”
Section: Discussionmentioning
confidence: 99%
“…16) Currently, several antagonists of CCL2 receptor CCR2 are under development for treatment of liver fibrosis, DN and MS. 14) However, despite extensive animal studies and clinical trials, the therapeutic potential of CCR2 antagonists remains inconclusive. For example, human monoclonal antibodies for CCL2 (ABN912) 17) and CCR2 (MLN-1202) 18) failed to show improvement in patients with RA, and rather increased C-reactive protein (CRP) levels at the highest dose of ABN912, while MLN-1202 successfully completed a phase II trial in patients with MS 19) and reduced CRP levels in patients at risk for atherosclerosis. 20) Furthermore, studies in nephrotoxic serum-induced glomerulonephritis models have indicated that special attention should be paid to CCL2 expression patterns in organs and time point for evaluation of therapeutic potential of test compounds.…”
mentioning
confidence: 99%
“…This rule is not as easily applied to RO assays given that large phycobiliproteins like APC and PE may interfere with each other due to steric hindrance or even lead to altered or aberrant fluorescence due to resonance energy transfer (22), often called F€ orster or fluorescent resonance energy transfer (FRET). Thus use of smaller organic dyes such as the Fluorescein isothiocyanate (FITC) and the Alex Fluor series, may be required for certain RO assay configurations provided that an adequate fluorescent signal can be obtained (8,23). The emerging class of small, polymer-based dyes (e.g.…”
Section: Fluorochrome Selectionmentioning
confidence: 99%